Characterization of the gene and mRNA of the large subunit of ribulose-1,5-bisphosphate carboxylase in pea plants. - Oishi, K K (1983)
mRNA coding for the large subunit (LS) of ribulose-1,5-bisphosphate carboxylase was obtained by fractionating chloroplast polysomes on an affinity column, using anti-ribulose-1,5-bisphosphate carboxylase immunoglobulin G. Approximately 20% of the polysomal RNA specifically bound to the affinity column. LS mRNA was also isolated by fractionating chloroplast polysomal RNA on sucrose gradients. The LS mRNA fraction was identified by translation in vitro followed by immunoprecipitation with anti-ribulose-1,5-bisphosphate carboxylase immunoglobulin G. Labeled LS mRNA was hybridized to a genomic digests of pea chloroplast DNA. The LS gene was localized on a 3.55-kilobase pair BamHI fragment in SalI-SmaI DNA fragment 4. The BamHI fragment containing the LS gene was cloned, and a restriction endonuclease map was constructed. The LS gene was localized on a 1.9-kbp KpnI-EcoRI fragment. The LS gene was analyzed by electron microscopy, using the R loop mapping technique. LS mRNA was colinear with the gene, and its size was 1.35 +/- 0.2 kilobase pairs. When the LS mRNA was analyzed on methylmercury agarose gels, it comigrated with the 16S rRNA. The direction of transcription of the LS gene was in the same direction as that of the rRNA genes.